Navigating the Future of Warfare: A Strategic Framework for Innovative Professional Military Education in the Era of Hybrid Threats - Budi Harijanto; Lukito Edi Nugroho; Subando Agus Margono; Ambar Teguh Sulistiyani (Jurnal Sosial Humaniora dan Pendidikan, 2025)
The character of global security is currently undergoing a paradigm shift, driven by the emergence of hybrid warfare and rapid technological disruptions. This dynamic necessitates a profound redefinition of military officer competencies. This study aims to analyze strategic transformation frameworks within Professional Military Education (PME), focusing on the integration of cognitive readiness and technological innovation. Employing a qualitative methodology with a systematic case study approach, the research evaluates the effectiveness of incorporating Artificial Intelligence (AI), virtual reality simulations, and adaptive learning environments into modern military curricula. The findings reveal a significant gap between traditional pedagogical models and the complex operational requirements of contemporary conflict zones. Specifically, the results suggest that technical proficiency alone is insufficient; rather, strategic success depends on enhanced critical thinking and decision-making under pressure. Consequently, this research proposes a human-centric educational framework that harmonizes digital literacy with strategic leadership soft skills. The implications provide a strategic roadmap for military academies to produce leaders capable of navigating the volatility, uncertainty, complexity, and ambiguity (VUCA) of future armed conflicts. Ultimately, this transformation is essential for maintaining strategic superiority and national defense resilience in an increasingly unstable global landscape.